If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 9(3x + -1) + -5 Reorder the terms: 6x = 9(-1 + 3x) + -5 6x = (-1 * 9 + 3x * 9) + -5 6x = (-9 + 27x) + -5 Reorder the terms: 6x = -9 + -5 + 27x Combine like terms: -9 + -5 = -14 6x = -14 + 27x Solving 6x = -14 + 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. 6x + -27x = -14 + 27x + -27x Combine like terms: 6x + -27x = -21x -21x = -14 + 27x + -27x Combine like terms: 27x + -27x = 0 -21x = -14 + 0 -21x = -14 Divide each side by '-21'. x = 0.6666666667 Simplifying x = 0.6666666667
| 3x+7=22 | | 7-0.2m=3 | | 5x-4=4x-13 | | 5x-4=4x+13 | | (x+3)(x-4)=52 | | 3+7(w+2)+w= | | x-8+x=y+x+x | | 5xw*8w= | | 8a*2a= | | 6c*9e= | | v*8x= | | 31.400+x=2.90x+x | | 2.75x=20+x | | 42+x=3.5x+x | | 1.909x=20+x | | 5x+15=-x+9 | | 5-x=-1 | | 3y+x=4 | | 86.65+x=4.7x+x | | 1.30x=20+x | | 45+x=3.5x+x | | 9(x+1)=3x+63 | | 40+x=3.25x+x | | 2x=20+x | | 110+x=6x+x | | 7.9x+9-2.9x=4 | | 2x-3(x+4)=(-5) | | 0.3x+18.2=x-9.45 | | 1.222x=20+x | | 2(3x-1.7)=3x-3.4 | | 18.5x=20+x | | 4(x+1.51)=3x |